Penelitian dalam Bidang Kedokteran Jiwa - Soejono Prawirohardjo Soejono Prawirohardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
The paper describes various methods of problem-solving during the history of mankind and puts special emphasis on discovering and identification of psychiatric problems. Research methodology in general is explained.Then it reviewed similarities between psychiatric research -- and the general, methodology. Finally, the particularities of psychiatric research are discussed.Key Words: research methodology -- psychiatric research -- gold standard diagnosis -- research instrument -- five levels model